Editors' Introduction to the Special Issue on Autonomic and Self-Adaptive Systems - Cámara, J.; Cuesta, C.; Pérez-Toledanov, M.Á. (Informatica)
Editors' Introduction to the Special Issue on Autonomic and Self-Adaptive Systems